Row ratio in maize (Zea mays) - legume intercropping in temperate valley condition - PANDITA, A K; SHAH, M H; BALI, AMARJIT S (The Indian Journal of Agricultural Sciences, 2013)
A field investigation was carried out during kharif 1995-96 on silty-clay loam soils of Shalimar to select out the compatible pulse crop for intercropping with maize and to find out suitable row ratio of maize and in intercropping system. Studies indicated that frencnchbean (Phaseolus-vulgaris-L.) was found better than greengram (Phaseolus radiatus L.) for intereropping with maize. The row ratio of 1 : 2 (maize-frenchbean) attained maximum grain yield, maize equivalent and land equivalent ratio (1.61). Results also revealed that association of frenchbean with maize crop improved availability of residual nitrogen in the soil and proved profitable with highest benelit:cost ratio (1.87).